Level of Good Adherence on Option B+ PMTCT and Associated Factors Among HIV Positive Pregnant and Lactating Mothers in Public Health Facilities of Ilu Abba Bor and Buno Bedele Zones, Oromia Regional State, Southwestern Ethiopia, 2018 - Yeshialem Asefa E (Dove Medical Press, 2020)
Eyosiyas Yeshialem Asefa,1 Dejene Edosa Dirirsa2 1Department of Midwifery, College of Health Science, Debre Birhan University, Debre Birhan, Ethiopia; 2Department of Midwifery, Public Health, and Medical Science Faculty, Mettu University, Mettu, EthiopiaCorrespondence: Eyosiyas Yeshialem Asefa Email eyosi143@gmail.comBackground: PMTCT programs help safe delivery practices and recommended infant feeding, as well as providing ART for infants exposed to HIV after birth for prevention and effective treatment. PMTCT service helps to reduce about 1.4 million HIV infections among children between 2010 and 2018. This study aimed to assess the good adherence level and associated factors of option B+ PMTCT among HIV-positive pregnant and lactating women in public health facilities of Ilu Abba Bor and Buno Bedele zones, Oromia regional state, Southwestern Ethiopia 2018.Methodology: Institutional-based cross-sectional study design was implemented to investigate the level of good adherence to option B+ PMTCT and possible predictors. A simple random sampling technique was used to interview a total of 180 mothers using the interviewer-guided questionnaire for data collection. Data were entered into EpiData version 3.1 and analyzed by SPSS version 23.0 statistical software. Descriptive statistics and logistic regression were computed to identify and see the relative effect of predictors on the outcome variable.Results: In this study, 146 (81.1%) of the study participants had good adherence to PMTCT option B+. Women who received social and financial support from friends, family members, and partners had good adherence to PMTCT option B+ than their counterparts. Similarly, women who disclosed their HIV status to others had good adherence than those who did not expose their status to their friends and parents.Conclusion and Recommendation: This study identified the overall level of PMTCT option B+ adherence level in the study area to be good compared to the national and some other findings. Providing support and encouraging a woman for disclosing their HV status for partners and families are very important to increase the adherence level of option B+.Keywords: adherence, HIV, lactating women, social support, disclosure